2017
DOI: 10.1111/aogs.13265
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index as a predictor for delivery method

Abstract: Prepregnancy BMI ≥30 was an independent risk factor for delivery by emergency cesarean section for both primiparous and parous women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
1
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 19 publications
4
19
1
2
Order By: Relevance
“…Since the most frequently mentioned reason for fear of labor pain in Iranian women is related to hospital equipment and low quality of care (48), it seems that promoting and implementing new low pain methods of vaginal delivery, such as the introduction of water birth, can be effective in reducing C-section rates. The present study showed that having a history of C-section increases the tendency for this mode of delivery, which is consistent with the results of some other studies (16,49). A study performed in Dutch reported a success rate of 60% -80% for vaginal delivery after C-section (19,50).…”
Section: Discussionsupporting
confidence: 92%
“…Since the most frequently mentioned reason for fear of labor pain in Iranian women is related to hospital equipment and low quality of care (48), it seems that promoting and implementing new low pain methods of vaginal delivery, such as the introduction of water birth, can be effective in reducing C-section rates. The present study showed that having a history of C-section increases the tendency for this mode of delivery, which is consistent with the results of some other studies (16,49). A study performed in Dutch reported a success rate of 60% -80% for vaginal delivery after C-section (19,50).…”
Section: Discussionsupporting
confidence: 92%
“…In several studies, obesity or maternal overweight have been linked to complications during pregnancy, such as hypertensive disorders or macrosomia [24], that may increase the risk of C-section [1,25]. Regarding the data from our study, the increase in emergency C-section rates may be related not only to the factors previously indicated, but also to the increase in altered fetal heart rate frequency and the higher rate of cephalopelvic disproportion in this population.…”
Section: Discussionsupporting
confidence: 55%
“…However, some studies point to abnormalities in uterine contractility and an increase in fat deposits in the soft areas of the pelvis [26]. This increase in C-section rates has already been described in other studies [1,10,24,25,27] and may also influence the risk of neonatal complications and the possibilities of newborn admission.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Infants who are small for gestational age due to tobacco abuse or insufficient maternal weight gain are also at risk for obesity and metabolic disease in childhood. Other exposures that can result in obesogenic epigenetic changes include but not are limited to: toxins, nutrition, medications, antibiotics, infection, and exogenous hormones (810).…”
Section: Initial Assessmentmentioning
confidence: 99%